Why I Can’t, Won’t or Don’t Test for HIV: Insights from Australian Migrants Born in Sub-Saharan Africa, Southeast Asia and Northeast Asia - Gray, Corie; Lobo, Roanna; Narciso, L.; Oudih, E.; Gunaratnam, P.; Thorpe, R.; Crawford, Gemma (MDPI, 2019)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. People born in sub-Saharan Africa and Southeast Asia are overrepresented in HIV notifications in Australia. Just under half of all notifications among people from sub-Saharan Africa and Southeast Asia are diagnosed late. Increased HIV testing among these communities is necessary to ensure early diagnosis, better care and reduce likelihood of HIV onward transmission. Recently, Australia has made new HIV testing methods available: rapid HIV testing and self-testing kits. We conducted 11 focus groups with 77 participants with people from sub-Saharan Africa, Southeast Asia and Northeast Asia in four jurisdictions in Australia. Focus groups discussed barriers to HIV testing and the acceptability of new testing methods. Barriers to HIV testing included: cost and eligibility of health services, low visibility of HIV in Australia, HIV-related stigma, and missed opportunities by general practitioners (GPs) for early diagnosis of HIV and linkage into care. Participants had low levels of knowledge on where to test for HIV and the different methods available. Diverse opportunities for testing were considered important. Interventions to increase HIV testing rates among sub-Saharan African, Southeast Asia and Northeast Asian migrants in Australia need to be multi-strategic and aimed at individual, community and policy levels. New methods of HIV testing, including rapid HIV testing and self-testing, present an opportunity to engage with migrants outside of traditional health care settings.